Alterative art versions of the past in contemporary literature: an attempt of typology (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
This article analyzes the problem of reality and literature interrelation and the problem of man and history relations. The research of the transcultural communica-tions in the artistic space, allows to define modern aesthetics as the universalistic func-tions. Such approach underlines research of modern variations of genre co-operation of form of novel and short story. Underlined narrative hierarchies' nuance peculiarities at the corresponding levels of fiction communication contribute to exposure of a artistic potential of historical prose works.
Keywords: history; interpretation post-modernism; alternative analog